Perkembangan Daerah Otonom Baru (DOB) di Provinsi Lampung (Model Tipologi Klassen) - Ambya Ambya (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
Considerations of the district area to divide include, among others, the existence of group similarities (preference for homogeneity), and social ties in one ethnicity (historical ethnic) believed to be able to realize shared prosperity. This study aims to see the development of DOB, which is grouped with theModel criteria Klassen Typology. The variable used is the income per capita with the rate of economic growth of new autonomous regions compared to provinces. The results show that all DOB belong to the relatively disadvantaged regional groups, except in East Lampung Regency. The relatively young new autonomous regions cause this condition. Their potential has not been fully managed to the maximum due to the limitations of the region, especially regional finance.